Sustainable Development From the Family to the Society - Gunay, Gulay; Oguz, Ahmet (Mediterranean Journal of Social Sciences, 2012)
â€œSustainabilityâ€ means the consideration of economical expectations with environmental and social concerns. This studyexamines individualâ€™s sustainable consumption behavior. Participations of this study consist of individuals who have married and live withhis/her family in KarabÃ¼k, Turkey. The sample size is determined using a random sampling method (n=500). Behaviors of individualstowards sustainable consumption was measured with â€œSustainable Consumption Behavior Scale (SCBs)â€ developed by KiracÄ± andKaralar (2010). Scale consists of 36 items. Beside descriptive statistics, t-test and one way variance analysis (ANOVA) is used in theanalysis of the data. According to the results of the study, it was found that frequency of SCBs was mid-level (=2.83). Analysis ofvariance tests show significant differences (p<.05) in perceptions of sustainable consumption behavior to gender, and socio-economiclevel, education and occupation. The results of this research have significant implications for policymakers and educators in their searchof strategies for improving the roles of familiesâ€™ to sustainable development. The ability to act as a responsible and democratic citizen isa prerequisite for a sustainable development. This skill can be improved by reaching the recent knowledge and lifelong learning.